NtHash: recursive nucleotide hashing. (16th July 2016) - Mohamadi, Hamid; Chu, Justin; Vandervalk, Benjamin P.; Birol, Inanc
Abstract : Motivation : Hashing has been widely used for indexing, querying and rapid similarity search in many bioinformatics applications, including sequence alignment, genome and transcriptome assembly, k -mer counting and error correction. Hence, expediting hashing operations would have a substantial impact in the field, making bioinformatics applications faster and more efficient. Results : We present ntHash, a hashing algorithm tuned for processing DNA/RNA sequences. It performs the best when calculating hash values for adjacent k -mers in an input sequence, operating an order of magnitude faster than the best performing alternatives in typical use cases. Availability and implementation : ntHash is available online at http://www.bcgsc.ca/platform/bioinfo/software/nthash and is free for academic use. Contacts : hmohamadi@bcgsc.ca or ibirol@bcgsc.ca Supplementary information: Supplementary data are available at Bioinformatics online.